Large scale and regional demographic responses to climatic changes in Europe during the Final Palaeolithic - Isabell Schmidt; Birgit Gehlen; Katja Winkler; Alvaro Arrizabalaga; Nico Arts; Nuno Bicho; Philippe Crombé; Berit Valentin Eriksen; Sonja B. Grimm; Katarina Kapustka; Mathieu Langlais; Ludovic Mevel; et al. (PLoS ONE, 2025)
The European Final Palaeolithic witnessed marked changes in almost all societal domains. Despite a rich body of evidence, our knowledge of human palaeodemographic processes and regional population dynamics still needs to be improved. In this study, we present regionally differentiated population estimates for the Greenland Interstadial 1d-a (GI-1d-a; 14-12.7 ka cal BP) and the Greenland Stadial 1 (GS-1; 12.7-11.6 ka cal BP) for Southern, Western, Northern and Central Europe. The data were obtained by applying the Cologne Protocol, a geostatistical approach for estimating prehistoric population size and density, to a newly compiled dataset of Final Palaeolithic sites. On a large spatio-temporal scale and compared to preceding Upper Palaeolithic phases, areas north of the Alps become the dominant demographic growth area for the first time since the dispersal of anatomically modern humans into Europe. At smaller scales, we observe divergent regional trends, with a conspicuous lack of archaeological evidence appearing in previously occupied areas of central France and Germany. Our study also shows that during the Final Palaeolithic, the climatic cooling of GS-1 coincides with a pronounced population decline in most parts of the study area. An apparent increase in population density occurs only in north-eastern Central Europe and north-eastern Italy. Our estimates suggest that the total population was reduced by half. Similar results, with a relationship between decreasing temperatures and decreasing populations, have already been observed for the late phase of the Gravettian, when populations were reduced to only one third of those estimated for the early phase. Yet, in contrast to the collapse of local populations during the late Gravettian, the increase in population densities in Central Europe during GS-1 indicates population movements eastwards, possibly in response to deteriorating climatic conditions, particularly in western regions during the Younger Dryas.